Medium-Mn steels for hot forming application in the automotive industry - Li, Shuo-shuo; Luo, Hai-wen (International journal of minerals, metallurgy and materials, 2021)
Advanced high-strength steels have been widely used to improve the crashworthiness and lightweight of vehicles. Different from the popular cold stamping, hot forming of boron-alloyed manganese steels, such as 22MnB5, could produce ultra-high-strength steel parts without springback and with accurate control of dimensions. Moreover, hot-formed medium-Mn steels could have many advantages, including better mechanical properties and lower production cost, over hot-formed 22MnB5. This paper reviews the hot forming process in the automotive industry, hot-formed steel grades, and medium-Mn steel grades and their application in hot forming in depth. In particular, the adaptabilities of medium-Mn steels and the presently popular 22MnB5 into hot forming were compared thoroughly. Future research should focus on the technological issues encountered in hot forming of medium-Mn steels to promote their commercialization.